Towards characterization of DNA structure under physiological conditions in vivo at the single-molecule level using single-pair FRET - Fessl, Tomás; Adamec, Frantisek; Polívka, Tomás; Foldynová-Trantírková, Silvie; Vácha, Frantisek; Trantírek, Lukás (Nucleic acids research, 2012)
Fluorescence resonance energy transfer (FRET) under in vivo conditions is a well-established technique for the evaluation of populations of protein bound/unbound nucleic acid (NA) molecules or NA hybridization kinetics. However, in vivo FRET has not been applied to in vivo quantitative conformational analysis of NA thus far. Here we explored parameters critical for characterization of NA structure using single-pair (sp)FRET in the complex cellular environment of a living Escherichia coli cell. Our measurements showed that the fluorophore properties in the cellular environment differed from those acquired under in vitro conditions. The precision for the interprobe distance determination from FRET efficiency values acquired in vivo was found lower (≈ 31%) compared to that acquired in diluted buffers (13%). Our numerical simulations suggest that despite its low precision, the in-cell FRET measurements can be successfully applied to discriminate among various structural models. The main advantage of the in-cell spFRET setup presented here over other established techniques allowing conformational analysis in vivo is that it allows investigation of NA structure in various cell types and in a native cellular environment, which is not disturbed by either introduced bulk NA or by the use of chemical transfectants.
Keywords: DNA; rezonanční přenos fluorescenční energie; Nucleic Acid Conformation; fluorescenční barviva; Fluorescence Resonance Energy Transfer; Escherichia coli; Fluorescent Dyes; konformace nukleové kyseliny